An emerging trend in Novel Psychoactive Substances (NPSs): designer THC - Cristian Caprari; Elena Ferri; Maria Angela Vandelli; Cinzia Citti; Giuseppe Cannazza (BMC, 2024)
Abstract Since its discovery as one of the main components of cannabis and its affinity towards the cannabinoid receptor CB1, serving as a means to exert its psychoactivity, Δ9-tetrahydrocannabinol (Δ9-THC) has inspired medicinal chemists throughout history to create more potent derivatives. Initially, the goal was to synthesize chemical probes for investigating the molecular mechanisms behind the pharmacology of Δ9-THC and finding potential medical applications. The unintended consequence of this noble intent has been the proliferation of these compounds for recreational use. This review comprehensively covers the most exhaustive number of THC-like cannabinoids circulating on the recreational market. It provides information on the chemistry, synthesis, pharmacology, analytical assessment, and experiences related to the psychoactive effects reported by recreational users on online forums. Some of these compounds can be found in natural cannabis, albeit in trace amounts, while others are entirely artificial. Moreover, to circumvent legal issues, many manufacturers resort to semi-synthetic processes starting from legal products extracted from hemp, such as cannabidiol (CBD). Despite the aim to encompass all known THC-like molecules, new species emerge on the drug users' pipeline each month. Beyond posing a significantly high public health risk due to unpredictable and unknown side effects, scientific research consistently lags behind the rapidly evolving recreational market.